2022
DOI: 10.1021/acs.bioconjchem.2c00038
|View full text |Cite
|
Sign up to set email alerts
|

[213Bi]Bi3+/[111In]In3+-neunpa-cycMSH: Theranostic Radiopharmaceutical Targeting Melanoma─Structural, Radiochemical, and Biological Evaluation

Abstract: With the emergence of [ 225 Ac]Ac 3+ as a therapeutic radionuclide for targeted α therapy (TAT), access to clinical quantities of the potent, short-lived α-emitter [ 213 Bi]Bi 3+ (t 1/2 = 45.6 min) will increase over the next decade. With this in mind, the nonadentate chelator, H 4 neunpa-NH 2 , has been investigated as a ligand for chelation of [ 213 Bi]Bi 3+ in combination with [ 111 In]In 3+ as a suitable radionuclidic pair for TAT and single photon emission computed tomography (SPECT) diagnostics. Nuclear … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 55 publications
2
6
0
Order By: Relevance
“…In the case of bioconjugate ( 17 ), the radiolabeling studies showed poorer RCCs with both [ 225 Ac]­Ac 3+ and [ 111 In]­In 3+ compared to the “free” chelator ( 14 ), while bioconjugate ( 19 ) showed more competitive complexation at low concentrations. This observation is consistent with the results previously reported for H 4 neunpa, which showed superior radiolabeling with [ 213 Bi]­Bi 3+ and [ 111 In]­In 3+ for bioconjugates featuring the elongated Aoc spacer between the chelator and CycMSH hex targeting vector.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…In the case of bioconjugate ( 17 ), the radiolabeling studies showed poorer RCCs with both [ 225 Ac]­Ac 3+ and [ 111 In]­In 3+ compared to the “free” chelator ( 14 ), while bioconjugate ( 19 ) showed more competitive complexation at low concentrations. This observation is consistent with the results previously reported for H 4 neunpa, which showed superior radiolabeling with [ 213 Bi]­Bi 3+ and [ 111 In]­In 3+ for bioconjugates featuring the elongated Aoc spacer between the chelator and CycMSH hex targeting vector.…”
Section: Resultssupporting
confidence: 93%
“…While the in vivo studies of [ 111 In]­[In­(picoopa-Bn-Aoc-Pip-Nle-CycMSH hex )] − were somewhat disappointing from an imaging perspective, these results are directly comparable to the previously reported radiotracer [ 111 In]­[In­(neunpa-Ph-Aoc-Pip-Nle-CycMSH hex )] − , which showed similarly high uptake in the liver (24.44 ± 4.99 %ID/g), spleen (28.67 ± 5.67 %ID/g), and kidneys (7.75 ± 0.37 %ID/g), and low tumor accumulation (1.64 ± 0.30 %ID/g) at 24 h post-administration . Free [ 111 In]­In 3+ is rapidly bound by human transferrin in vivo and transported to the liver and spleen; however, the [ 111 In]­[In­(neunpa)] − complex has been previously shown to remain stable in vivo up to 5 days post-administration .…”
Section: Resultssupporting
confidence: 76%
“…H 4 neunpa shows the highest RCY for bismuth labeling, and quantitative complex formation was reported for very small amounts of this chelator (10 −8 M) at ambient temperature after incubation for 5−7 min. 17 However, both bispidines allow labeling at remarkably high molar activities, with values of 0.25 MBq/nmol for L 2 and 2.5 MBq/nmol for L 3 . Quantitative radiolabeling with [ 133 La]LaCl 3 was achieved with 10 μmol/L L 2 at a slightly increased temperature (40 °C) after incubation for 60 min (Figure 6).…”
Section: Solution Structures Of [Lamentioning
confidence: 99%
“…16,17 Specifically with [ 225 Ac]Ac 3+ , complexation requires up to half an hour at 80 °C for quantitative labeling, and this is not suitable for use with heat-sensitive targeting moieties such as antibodies. 17 Faster complexation under mild conditions is achieved with the open-chain and macrocyclic patype ligands (pa = picolinic acid). 16−18 Ligands with the bispidine backbone (e.g., L 1 −L 3 ) are known to be favorable with respect to metal ion selectivity, high complex stability, efficient complexation kinetics, and inertness, 19 and this is due to their open-chain nature, a rigid cavity with a favorable size and shape, in particular for tetragonal symmetry and relatively large metal ions (see Figure 1), 20,21 and due to the possibility of decorating the scaffold with pendant donor groups with well-tuned electronic and geometric properties.…”
Section: ■ Introductionmentioning
confidence: 99%
“…12 This is inherently difficult to implement, especially for the radiolabeling with metal-ions and metalloids, which are usually separated under highly acidic conditions (2–12 M HCl) 13,14 from their parent nuclide using ion-exchange chromatography but subsequently require much milder, aqueous radiosynthesis conditions for stable chelate formation. 15–17 Specifically, bifunctional chelators, peptides and biomolecules utilized as disease-specific targeting vectors typically require a pH range of 4–8 to form stable complexes. 18–22…”
Section: Introductionmentioning
confidence: 99%